BREAK EVEN ANALYSIS OF BROILER PRODUCTION IN THE ACCRA-TEMA AND KUMASI AREAS - Mahama, E.A.; Andah, E.K.; Amegashie, D.P.K.; Mensah-Bonsu, A. (European Scientific Journal, ESJ, 2013)
The paper examines the profitability of broiler production, using the break even concept. The break even quantities, net present values and internal rates of returns have been estimated for 20 selected poultry farms. Poultry farms located in Kumasi area broke even in the production of broiler while about 38.5 percent of the farms in Accra-Tema area produced below their break even levels. Only 30 percent of the farms registered positive net present value. Under an interest rate scenario of 25 percent about 70 percent of all farms, would be profitable (break even). The results suggest that lower interest rate is essential for more farms to break even (be competitive) and stay in the poultry business.